2021
DOI: 10.1007/s00204-020-02965-2
|View full text |Cite
|
Sign up to set email alerts
|

The enzyme subunit SubA of Shiga toxin-producing E. coli strains demonstrates comparable intracellular transport and cytotoxic activity as the holotoxin SubAB in HeLa and HCT116 cells in vitro

Abstract: The subtilase cytotoxin (SubAB) is secreted by certain Shiga toxin-producing Escherichia coli (STEC) strains and is composed of the enzymatically active subunit SubA and the pentameric binding/transport subunit SubB. We previously demonstrated that SubA (10 µg/ml), in the absence of SubB, binds and intoxicates the human cervix cancer-derived epithelial cell line HeLa. However, the cellular and molecular mechanisms underlying the cytotoxic activity of SubA in the absence of SubB remained unclear. In the present… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(10 citation statements)
references
References 20 publications
0
10
0
Order By: Relevance
“…However Western blot experiments by Funk et al showed a concentration-dependent SubA binding to HeLa cells in the absence of SubB [8]. Cell surface binding of SubA was confirmed by flow cytometry [9], but to the best of our knowledge, a specific SubA receptor has yet not been identified. Since BiP/GRP78, the molecular substrate of SubA protease in the ER, is also present at the cell surface [20], it can be speculated that cell surface bound GRP78 might be a potential SubA receptor.…”
Section: Cellular Uptake and Cytotoxic Activity Of The Enzyme Subunit...mentioning
confidence: 94%
See 4 more Smart Citations
“…However Western blot experiments by Funk et al showed a concentration-dependent SubA binding to HeLa cells in the absence of SubB [8]. Cell surface binding of SubA was confirmed by flow cytometry [9], but to the best of our knowledge, a specific SubA receptor has yet not been identified. Since BiP/GRP78, the molecular substrate of SubA protease in the ER, is also present at the cell surface [20], it can be speculated that cell surface bound GRP78 might be a potential SubA receptor.…”
Section: Cellular Uptake and Cytotoxic Activity Of The Enzyme Subunit...mentioning
confidence: 94%
“…In the ER, SubA exhibits its enzyme activity and cleaves BiP/GRP78. However, BiP/GRP78 cleavage was delayed when cells were treated with SubA alone compared to SubAB [8,9]. To reach the ER, SubA alone seems to take the same overall route as SubAB via the retrograde trafficking pathway [9] (Figure 2).…”
Section: Cellular Uptake and Cytotoxic Activity Of The Enzyme Subunit...mentioning
confidence: 99%
See 3 more Smart Citations